(untitled) (Comprehensive Journal of Science, 2025)
This study aims to assess the extent to which accounting education quality standards are applied within technical education institutions in Tripoli, Libya, from the perspective of faculty members, The research emerges in response to persistent challenges facing accounting education in Libya, including limited alignment with international standards and institutional deficiencies in curriculum development and quality assurance mechanisms, A descriptive -analytical methodology was adopted, utilizing a structured questionnaire comprising 18 items distributed to a comprehensive sample of accounting faculty, A total of 26 valid responses were analyzed. Findings revealed that the overall level of quality standards implementation is moderate to weak, with mean scores ranging between 2.12 and 2.51 According to the study’s scale, Inferential statistical analysis showed no significant differences in perceptions based on academic qualification or years of experience, However, statistically significant differences were found based on academic rank and professional training, indicating that more senior and trained faculty members demonstrate greater awareness and critical evaluation of quality practices. The study recommends enhancing faculty involvement in curriculum development, providing continuous professional training, activating stakeholder feedback mechanisms, and aligning academic programs with international standards such as IAES and AACSB, These measures are essential to improving the quality of accounting education and strengthening graduate readiness for both local and global labor markets.